SMEs IN THE ACTUAL CONTEXT - Catalina IANASI; Minodora-Maria PASARE (Fiabilitate şi Durabilitate)
In the current economic context, many companies have encountered problems in maintaining their business or have failed to maintain their business and have suffered heavy losses and closed down. Many entrepreneurs have reduced their activity and implicitly the staff number. Others have managed to orient to new categories of consumers and to adapt the activity to their requirements, maintaining the company's activity in a profitable way.